Constraints in Production of Orange (Citrus reticulata Blanco) in Vidharbha Region of Maharashtra - Gedam, Praveen; Singh, Baldeo (Indian Journal of Extension Education, 2012)
The present study was conducted in Vidharbha region of Maharashtra with specific objectives to study the constraints  faced by orange (Citrus reticulata Blanco) growers in cultivation and marketing and to provide suggestions offered by  growers to overcome these constraints. Three districts, namely Nagpur, Amaravati and Wardha, purposively selected and  from each district two blocks and from each block two villages were randomly selected. Ten farmers from each village  were selected randomly to make 120 samples. The major constraints were high incidence of disease, frequent shedding of  electricity, lack of disease resistant varieties and lack of information regarding improved orange variety. High fluctuation  of price, price not according to quality of produce, lack of cold-storage facilities and more commission charged by  commission agents. The important suggestion offered by growers were: establishment of cold storage facilities at village  level, easy accessibility of credit with low interest rate and timely electricity supply with low cost, establishment of  processing industries at production-catchments area, establishment of co-operative marketing agencies, government  support during crop failure and lower down the commission charged by APMCs.
Keywords: Co-operative; constraints; implication